Maximizing Curcuminoid Extraction from Curcuma aromatica Salisb. Rhizomes via Environmentally Friendly Microwave-Assisted Extraction Technique Using Full Factorial Design - Jirapornchai Suksaeree; Chaowalit Monton (International Journal of Food Science)
Curcuma aromatica Salisb. contains a high content of curcuminoids, which can be utilized for cosmetic purposes. The objective of this study was to optimize the extraction conditions of C. aromatica rhizomes in castor oil to maximize curcuminoid content using a simple and environmentally friendly microwave-assisted extraction method. A 32 full factorial design was employed, with two factors—microwave power and time—varying between 600-800 W and 30-90 s, respectively. Five responses were monitored, including extraction yield, bisdemethoxycurcumin, demethoxycurcumin, curcumin, and total curcuminoid contents. The results demonstrated that increasing microwave power and time led to an increase in all five responses. The optimal condition, which simultaneously maximized extraction yield and total curcuminoid content, was achieved at a microwave power of 800 W for 90 s. This condition resulted in an extraction yield of 71.020%, bisdemethoxycurcumin content of 0.036%, demethoxycurcumin content of 0.210%, curcumin content of 0.080%, and total curcuminoid content of 0.326%. The computer program accurately predicted the results with a percentage error of less than 2%. Stability data revealed that the total curcuminoid content remained stable with a percentage remaining above 90% when stored at 4°C, 30°C±75%RH, and 40°C±75%RH for three months. In summary, this study successfully applied a full factorial design to maximize curcuminoid extraction from C. aromatica rhizomes using an environmentally friendly microwave-assisted extraction method for cosmetic purposes.